An assessment of residence hall students' behaviors and attitudes related to racial diversity - Basden, Kelly S. (Kansas State University, 2008)
This report highlights the results of a revised diversity survey that was designed to assess the behaviors and attitudes of students who live in the residence halls at Kansas State University (K-State) regarding their interactions with people from diverse backgrounds. Diverse backgrounds, for the purpose of this study, are specifically related to a racial background different than their own. A survey of 25 questions was distributed to every residence hall student via email. The survey that was distributed was adapted from a version that was used previously by the Department of Housing & Dining Services at K-State. The original survey was based on the Michael P. Tilford competencies that were compiled in 2000-2001 by K-State's Tilford Group. The Tilford competencies are all based on students' multicultural competency. Multicultural competency is defined by the K-State Tilford group as the knowledge, skills and personal attributes needed to live and to work in a diverse world. (K-State Tilford Group, 2007) The revised survey focuses heavily on the skills portion of the Michael P. Tilford competencies and is based on students' self-report.
Keywords: Residence Halls; Racial Diversity; Attitudes; Behaviors; Education, Educational Psychology (0525); Education, Guidance and Counseling (0519); Education, Higher (0745)